Pancreatic extracorporeal shock wave lithotripsy: a key technology truly improves treatment model for pancreatic stones - Yi Jinhui; Xu Jinjie; Hu Lianghao (Medical Review)
Chronic pancreatitis (CP) is characterized by irreversible destruction of pancreatic parenchyma, inflammatory cell infiltration and progressive fibrosis of pancreatic tissue. Obstruction of pancreatic duct by pancreatic stone is the common pathological change in the course of CP with the incidence of over 50 % at the diagnosis of CP. These ductal stones would cause pancreatic parenchymal hypertension and local ischemia, which was eventually followed by recurrent episodes of painful pancreatitis or other manifestations of pancreatic exocrine and endocrine insufficiency. Removing pancreatic stones has been confirmed as the core to reduce pressure, improve drainage and lessen pain. Surgical therapy achieves satisfying pain relief with more complications, higher cost and less repeatability compared with endoscopic therapy. Endoscopic retrograde cholangiopancreatography, which used to be the standard endoscopic therapy for pancreatic stones, would fail if these stones are large or complex, while pancreatic extracorporeal shock wave lithotripsy (P-ESWL), which has been applied since 1987, could overcome this problem. Up to now, a large number of guidelines have recommended the P-ESWL as the first-line treatment strategy for radiopaque obstructive main pancreatic duct stones larger than 5 mm located in the head/body of the pancreas, and P-ESWL had completely changed the traditional treatment model for CP patients with pancreatic stones. In this article, we will focus on the technical progress, efficacy, safety and potential research areas of P-ESWL, we also give us suggestions for lithotripters improvement.